2010
DOI: 10.1136/bjsm.2010.078972.57
|View full text |Cite
|
Sign up to set email alerts
|

Previous high-intensity activity affects lower limb strength ratios

Abstract: Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 1 2 2 2/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t h e f o l l o w i n g f a i r u s a g e g u i d e l i n e s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, this assessment does not provide information on imbalance changes after repeated muscular contractions. In a recent study of Bampouras (2010), the author suggested that the results indicate that high intensity activity increases lower limb strength imbalance. The implication of this research, according to authors, is that assessment activities conducted during the rested state may not accurately reflect the true strength difference between limbs, leading to inaccurate training or rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assessment does not provide information on imbalance changes after repeated muscular contractions. In a recent study of Bampouras (2010), the author suggested that the results indicate that high intensity activity increases lower limb strength imbalance. The implication of this research, according to authors, is that assessment activities conducted during the rested state may not accurately reflect the true strength difference between limbs, leading to inaccurate training or rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Sprint and explosive power are basic skills in most athletic sports disciplines; therefore assessing strength values is crucial for evaluating the muscular performance and function [5].…”
Section: Introductionmentioning
confidence: 99%